Resolution of some nomenclatural issues in the Cetoniinae, Dynastinae, Hopliinae, Melolonthinae, Pachydeminae and Sericinae (Coleoptera: Scarabaeidae) - Allsopp, Peter G.; Schoolmeesters, Paul (Zootaxa, 2024)
Replacement names are proposed for the following six genera: Ahrenserica Allsopp & Schoolmeesters, replacement name for Orthoserica Brenske, 1900 (Sericini); Brenskecnemus Allsopp & Schoolmeesters, replacement name for Holocnemus Brenske, 1894 (Melolonthini); Dombrocnemis Allsopp & Schoolmeesters, replacement name for Toxocnemis Dombrow, 2002 (Hopliini); Lazomba Allsopp & Schoolmeesters, replacement name for Zomba Lacroix, 2006 (Pachydemini); Perabula Allsopp & Schoolmeesters, replacement name for Rabula Péringuey, 1902 (Hopliini); Phillsoppia Allsopp & Schoolmeesters, replacement name for Leptocnemis Dombrow, 2001 (Hopliini). Rabula morosa Péringuey, 1902 is designated as the type species of Perabula. Miotemna Lacordaire, 1856 is an unnecessary replacement name for Octotemna Blanchard, 1850 (Sericini). Aceratus Endrődi, 1969 (Pentodontini) and Desfontainesia Alexis & Delpont, 2001 (Goliathini) are shown to be the valid author citations.